Business, BTEC National Level 3. Book 1 - Bevan, John (Writer of Business study skills guide); Coupland-Smith, Helen; Dransfield, Robert, 1952-; Goymer, John; Richards, Catherine (Writer on business education) (2010)
This student book includes all four mandatory units plus eight popular optional units providing complete coverage for the BTEC Level 3 National Supplementary Award. Assignment activities give practice for all grading criteria for the units covered, with Edexcel's own assessment tips written by BTEC Level 3 National experts.
At head of title: Edexcel.
Includes bibliographical references and index.
Keywords: Business; Business and Management